2017
DOI: 10.1093/pubmed/fdx066
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality and impact of public health social media activity in Scotland during 2016: #ScotPublicHealth

Abstract: The quality and impact of tweets sent by the Scottish Public Health community was higher during 2016 than previous years. Conference tweeting remains an area for improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Professionals, pharmaceutical companies and biotech investors all tweeted about the congress. A more recent cancer conference in the UK (#NCRI2018) did not identify pharmaceutical or biotech tweeters among its top influencers in a NodeXL extract 17. Analysis of previous conferences on other topics, including infectious diseases and cardiology, has not illustrated a similar level of commercial influence 18–20…”
Section: Discussionmentioning
confidence: 98%
“…Professionals, pharmaceutical companies and biotech investors all tweeted about the congress. A more recent cancer conference in the UK (#NCRI2018) did not identify pharmaceutical or biotech tweeters among its top influencers in a NodeXL extract 17. Analysis of previous conferences on other topics, including infectious diseases and cardiology, has not illustrated a similar level of commercial influence 18–20…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that a small percentage of Twitter users typically generate the majority of the online content, with most users acting as silent observers. 7 This phenomenon is sometimes expressed as “The 90:9:1 Rule of Participation Inequality,” 8 which states that 90% of social media users are observers who do not contribute, 9% engage a little, with the remaining 1% accounting for almost all the action. In an effort to quantify the participation inequality at our meeting, we found that in both years 50% of the tweets could be attributed to approximately 10 users (2% of meeting attendees), with the remaining tweets contributed by approximately 350 users.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is easy to make an attempted connection using social media, and this might be expected to be the best way to attract new participants to a social media activity, real-world connections are also important. Repeated engagement through different approaches (online, in person, at meetings, by e-mail, and ultimately using webinars) was successful in recruiting a wider audience in the Scottish public health community 15 .…”
Section: Discussionmentioning
confidence: 99%